Copy number variations in alternative splicing gene networks impact lifespan. - Joseph T Glessner; Albert Vernon Smith; Saarene Panossian; Cecilia E Kim; Nagahide Takahashi; Kelly A Thomas; Fengxiang Wang; Kallyn Seidler; Tamara B Harris; Lenore J Launer; Brendan Keating; John Connolly; et al. (PLoS ONE)
Longevity has a strong genetic component evidenced by family-based studies. Lipoprotein metabolism, FOXO proteins, and insulin/IGF-1 signaling pathways in model systems have shown polygenic variations predisposing to shorter lifespan. To test the hypothesis that rare variants could influence lifespan, we compared the rates of CNVs in healthy children (0-18 years of age) with individuals 67 years or older. CNVs at a significantly higher frequency in the pediatric cohort were considered risk variants impacting lifespan, while those enriched in the geriatric cohort were considered longevity protective variants. We performed a whole-genome CNV analysis on 7,313 children and 2,701 adults of European ancestry genotyped with 302,108 SNP probes. Positive findings were evaluated in an independent cohort of 2,079 pediatric and 4,692 geriatric subjects. We detected 8 deletions and 10 duplications that were enriched in the pediatric group (P=3.33×10(-8)-1.6×10(-2) unadjusted), while only one duplication was enriched in the geriatric cohort (P=6.3×10(-4)). Population stratification correction resulted in 5 deletions and 3 duplications remaining significant (P=5.16×10(-5)-4.26×10(-2)) in the replication cohort. Three deletions and four duplications were significant combined (combined P=3.7×10(-4)-3.9×10(-2)). All associated loci were experimentally validated using qPCR. Evaluation of these genes for pathway enrichment demonstrated ~50% are involved in alternative splicing (P=0.0077 Benjamini and Hochberg corrected). We conclude that genetic variations disrupting RNA splicing could have long-term biological effects impacting lifespan.